PENDEKATAN KESEJAHTERAAN SEBAGAI STRATEGI PENGUATAN NASIONALISME MASYARAKAT DI KAWASAN PERBATASAN - Makarius Erwin Bria; Suharno Suharno (Universitas Negeri Malang, 2018)
This article aims to discuss the border situation in East Kobalima District, East Nusa Tenggara, which is far from the reach of the government. The low development potential in the border region triggers problems that affect the sense of nationalism. The method used is a qualitative approach type case study. This article discusses the welfare approach as a strategy implemented by the Border Management Agency of the East Nusa Tenggara Province to strengthen the nationalism of the border communities. The welfare approach implemented includes 1) infrastructure develop- ment and improvement; and 2) improving community welfare. Through a welfare approach, the community feels the presence of the state so that it can strengthen the spirit of nationalism and greater citizen loyalty to maintain the existence of Indonesianism in the border region.DOI: http://dx.doi.org/10.17977/um019v3i12018p081